FAKTOR FAKTOR YANG MEMENGARUHI MINAT BELI SUSU BUBUK KAMBING ETAWA DI DESA BAREGBEG KECAMATAN BAREGBEG KABUPATEN CIAMIS - Rega Ambawana; Agus Yuniawan Isyanto; Trisna Insan Noor (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2025)
This research was carried out with the aim of finding out the factors that influence interest in buying Etawa goat milk powder in Baregbeg Village, Baregbeg District, Ciamis Regency, the type of research used in this research is quantitative. The data collected includes primary data and secondary data. The sampling technique is carried out using the survey method and sampling uses the Slovin method, a formula or formula for calculating the number of samples from a population that is not known for certain. The sample studied was 45 community samples with the research limitation being only civil servants and entrepreneurs, the analysis method used was multiple linear regression. The research results show that the variables income, age, education and number of family dependents have a significant effect on interest in buying powdered milk. Partially, income, education and number of family dependents have a positive effect on buying interest, while age has no significant effect on buying interest. Kewords : Etawa Goat, Purschase Interest, Powdered Milk